Optimalisasi Penerbitan Surat Berharga Syariah Negara (SBSN) Pada Indstri Keuangan Syariah - Wahid, Alif Rodliya (AL-QARDH, 2019)
State Sukuk (Surat Berharga Syariah Negara) is an instrument of investment activities issued by the government. Sukuk can be used as a development of infrastructure that is primarily focused on advancing the nation